NEGATIVE PRESSURE WOUND THERAPY VERSUS CONVENTIONAL DRESSING IN MANAGEMENT OF NECROTIZING SOFT TISSUE INFECTIONS- A COMPARATIVE STUDY (Journal of Pharmaceutical Negative Results, 2022)
Active diagnosis and timely management is required in case of necrotising soft tissue infection. Negative pressure wound therapy (NPWT) is used in healing wounds as an adjunct method. Aim and objective: To validate advantages and efficiency of negative pressure wound therapy (NPWT) over povidone iodine dressing (PID) in treatment of the raw wound due to debridement of necrosed tissue. Methodology: Patients who had necrotizing soft tissue infections with necrosed tissues, for whom wound debridement was done. Prospective study for wound healing was done and was divided Weekly comparisons were done based on wound cultures, appearance of granulation tissue, by the reduction in surface area was measured using grid tracing method, and by seven weeks the patients were followed for closure of the raw area either by secondary intention or fit for Split skin grafting (STSG). Results: By the second week there was decrease of wound infections in 55% in NPWT group and 35% in CPID group with P=0.005 Just granulation tissue appeared in 75% of the NPWT group and only 35% in the CPID group with P=0.002 The average wound contraction was by 31% in NPWT group and 11% in CPID group with P=0.000. 85% wounds in NPWT completely healed in the NPWT group and only 55% in the CPID Group with P=0.005